1960
DOI: 10.1136/jcp.13.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Cytomegalic Inclusion-Body Disease Associated With Pneumocystis Pneumonia in Adults

Abstract: Three cases of generalized cytomegalic inclusion-body disease (salivary virus disease) in adults are reported, bringing the number of published cases up to 34. The infection is very rare in adults although well known in infants. As is often found in infants with this disease, pneumonia due toPneumocystis cariniiwas also present in each case.The first patient had Wegener's granulomatosis, which presented with acute otitis media: a review of histological material obtained at mastoidectomy eight weeks before deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1961
1961
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Cancers are one of the earliest identified underlying conditions associated with PCP, as first reported in late 1950s in patients with leukemia and Hodgkin’s disease [ 91 , 92 ]. Hematological malignancies (including various leukaemias and lymphomas as well as multiple myeloma) remain the most common underlying diseases predisposing patients to PCP, accounting for ~30–80% of PCP cases among non-HIV patients [ 10 , 29 , 31 ].…”
Section: Immunodeficient Conditions and Risk Factors For Pcpmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancers are one of the earliest identified underlying conditions associated with PCP, as first reported in late 1950s in patients with leukemia and Hodgkin’s disease [ 91 , 92 ]. Hematological malignancies (including various leukaemias and lymphomas as well as multiple myeloma) remain the most common underlying diseases predisposing patients to PCP, accounting for ~30–80% of PCP cases among non-HIV patients [ 10 , 29 , 31 ].…”
Section: Immunodeficient Conditions and Risk Factors For Pcpmentioning
confidence: 99%
“…GPA is a rare necrotizing vasculitis characterized by necrotizing granulomas and pauci-immune vasculitis that most commonly affects small- to medium-sized vessels in the respiratory tract and kidneys. The first case of PCP associated with GPA was reported in 1960 from a female American adult [ 92 ]. Based on multiple systematic reviews of data reported worldwide, GPA appears to be the most common AIID associated with PCP, with an estimated incidence of 6–20% [ 32 , 144 , 145 ].…”
Section: Immunodeficient Conditions and Risk Factors For Pcpmentioning
confidence: 99%
“…In these cases diagnosis during life is virtually impossible ( 6 ). Two forms occur, local or disseminated, but both appear to be associated with severe debilitating conditions which themselves are usually fatal.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…However, cytomegalovirus infection in a pregnant woman may also be associated with haematological changes and lesions in her lungs, kidneys, salivary and adrenal glands and spleen (Symmers, 1960;Plummer, 1973). Thus abortion, congenital deformity or foetal growth retardation in human babies may be mediated by any of three mechanisms, namely: 1.…”
mentioning
confidence: 99%